2016
DOI: 10.1007/s11187-016-9760-7
|View full text |Cite
|
Sign up to set email alerts
|

Innovation processes in family firms: the relevance of organizational flexibility

Abstract: The current study attempts to broaden our understanding of the processes underlying successful innovation in family firms by studying not only research and development (R&D) but also organizational flexibility as drivers of innovation performance. Building on existing theoretical and empirical work, we formulate hypotheses on the relationship between family ownership and R&D and organizational flexibility, and on how this translates into successful innovation. Using a sample of 2604 firms and 3140-year observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 76 publications
4
70
1
Order By: Relevance
“…The studies are also quite evenly distributed between primary and secondary data. In terms of geographical coverage, the studies cover a wide range of regions: Asia (Carney, 2005), Austria (Hatak & Hyslop, 2015), Belgium and Netherlands (Classen et al, 2012), China (Deng et al, 2013;Li et al, 2015), Emerging markets (Kim et al, 2004), across EU countries (Broekaert et al, 2016), Finland (Kontinen & Ojala, 2011;Kraus et al, 2012), France (Sirmon et al, 2008), Germany (Block & Spiegel, 2013;Harms et al, 2015), India (Pant & Rajadhyaksha, 1996;Singh & Gaur, 2013), Italy (Alberti et al, 2014;Cassia et al, 2012;Denicolai et al, 2015;Gurrieri, 2008;Pittino & Visintin, 2011;Pittino et al, 2013), Korea (Miller et al, 2009), Malaysia (Yeoh, 2014), Scotland (Anderson et al, 2005), Spain (Gómez-Mejía et al, 2007;Hausman, 2005;Nieto et al, 2015;Serrano-Bedia et al, 2016;Pérez, 2007), Taiwan (Tsao & Lien, 2013), and US (Hausman, 2005;Sorenson et al, 2008;Spriggs et al, 2012;Stanley & McDowell, 2014;Zahra, 2010).…”
Section: Methodological Empirical and Theoretical Issuesmentioning
confidence: 99%
“…The studies are also quite evenly distributed between primary and secondary data. In terms of geographical coverage, the studies cover a wide range of regions: Asia (Carney, 2005), Austria (Hatak & Hyslop, 2015), Belgium and Netherlands (Classen et al, 2012), China (Deng et al, 2013;Li et al, 2015), Emerging markets (Kim et al, 2004), across EU countries (Broekaert et al, 2016), Finland (Kontinen & Ojala, 2011;Kraus et al, 2012), France (Sirmon et al, 2008), Germany (Block & Spiegel, 2013;Harms et al, 2015), India (Pant & Rajadhyaksha, 1996;Singh & Gaur, 2013), Italy (Alberti et al, 2014;Cassia et al, 2012;Denicolai et al, 2015;Gurrieri, 2008;Pittino & Visintin, 2011;Pittino et al, 2013), Korea (Miller et al, 2009), Malaysia (Yeoh, 2014), Scotland (Anderson et al, 2005), Spain (Gómez-Mejía et al, 2007;Hausman, 2005;Nieto et al, 2015;Serrano-Bedia et al, 2016;Pérez, 2007), Taiwan (Tsao & Lien, 2013), and US (Hausman, 2005;Sorenson et al, 2008;Spriggs et al, 2012;Stanley & McDowell, 2014;Zahra, 2010).…”
Section: Methodological Empirical and Theoretical Issuesmentioning
confidence: 99%
“…Thus, managerial choices are driven by the desire to preserve and increase the family's SEW, that is, if SEW is threatened, family firms would make decisions to avoid the loss of SEW, in spite of their economic efficiency (Gottardo and Moisello 2015). Moreover, in the scant previous literature about flexibility in family firms, family influence has been described as a barrier to strategic flexibility (Broekaert et al 2016). This is because strategic flexibility is a context variable that can depend on the chief executive officer's (CEO) personality or team management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the papers analyzed, these elements were mostly treated as control variables. The industrial context was often found to affect entrepreneurship in different ways (e.g., Boling, Pieper, and Covin ; Broekaert, Andries, and Debackere ; Casillas, Moreno, and Barbero ): some industries, particularly high‐tech ones, were significantly and positively related to entrepreneurship (e.g., Broekaert, Andries, and Debackere ). Industry concentration (Classen et al ) and industry growth (e.g., Choi et al ; Cruz and Nordqvist ; Nieto, Santamaria, and Fernandez ) were also found to be conducive to entrepreneurship.…”
Section: Context‐level Antecedents Of Entrepreneurship In Family Firmsmentioning
confidence: 99%
“…The qualitative papers usually defined more complex frameworks that included steps, interactions, and various variables. Broekaert, Andries, and Debackere (2016), for example, focused on the processes that lead to successful innovation in family businesses and found that these were facilitated by organizational flexibility. Carnes and Ireland (2013) suggested that the sub-processes of the resource-bundling process-stabilizing, enriching, and pioneeringmediated the relationship between familiness and innovation.…”
Section: The Processes Of Entrepreneurship In Family Firmsmentioning
confidence: 99%